2019
DOI: 10.4274/tjo.galenos.2019.87059
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results in Patients with Combined Penetrating Keratoplasty and Vitreoretinal Surgery Using Landers Wide-field Temporary Keratoprosthesis

Abstract: Objectives:To evaluate the clinical results of combined pars plana vitrectomy (PPV) with Landers wide-field temporary keratoprosthesis and penetrating keratoplasty (PK).Materials and Methods:From January 2016, traumatic eyes with coexisting corneal and vitreoretinal diseases that underwent combined keratoprosthesis/PPV/PK surgery were retrospectively evaluated. Demographic characteristics, visual acuity (VA), intraocular pressure (IOP) and clinical findings of the cornea, lens, and retina were recorded during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Mayalı et al 26 conducted a study in which SO tamponade was used in all patients during combined surgery. Contrary to our results, however, they reported that SO did not significantly increase the risk of graft failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayalı et al 26 conducted a study in which SO tamponade was used in all patients during combined surgery. Contrary to our results, however, they reported that SO did not significantly increase the risk of graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by a variety of factors, including a large percentage of their patients having a postoperative pseudophakic status that could have reduced the probability of direct SO-endothelium contact, early removal of SO, and small sample size. 26 In addition, Watson et al 16 described a nonsignificant trend toward early graft failure in SO-filled eyes, and Lee et al 11 reported no significant effect of SO on graft survival. However, both discussed the benefits of further studies with longer follow-up and larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…In pathologies in which corneal and vitreoretinal pathologies coexist, the use of temporary keratoprosthesis (TKP) grants a clear view during pars plana vitrectomy (PPV), providing the same surgical properties as the standard vitreoretinal sur­gery. 5,6 The first TKP for PPV was described by Landers 7 who designed the wide-field TKP used nowadays. 8…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In pathologies in which corneal and vitreoretinal pathologies coexist, the use of temporary keratoprosthesis (TKP) grants a clear view during pars plana vitrectomy (PPV), providing the same surgical properties as the standard vitreoretinal surgery. 5,6 The first TKP for PPV was described by Landers 7 who designed the wide-field TKP used nowadays. 8 PK with PPV assisted by TKP has shown its advantages in ocular trauma and endophthalmitis cases, but the majority of the published studies include a limited number of infectious conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Significant disparities, particularly in terms of corneal graft survival, functional success, and complication rates, have been observed. [6][7][8] As each patient and case is unique, treatment options should be tailored to the patient's specific condition. In light of these considerations, this study examines the clinical characteristics and outcomes of patients who underwent combined PKP and PPV with the use of the Eckardt TKP.…”
mentioning
confidence: 99%